Design and development of smart interoperable electric vehicle supply equipment for electric mobility - Anju S. Pillai; Prajeesh C. Balakrishna (Institute of Advanced Engineering and Science, 2023)
The transportation industry at present is moving towards electrification and the number of electric vehicles in the market increased with the different policies of the directorate. Consumers, who wish to contribute to green mobility are concerned about the limited availability of charging points due to high manufacturing costs and the interoperability issues related to smart charging. This work proposes an Internet of things-based low-cost, interoperable smart electric vehicle supply equipment for deploying in all charging stations. The device hardware is designed to monitor, analyze, and collect consumed energy by the vehicle and transfer this data to a connected network. The pre-defined messages associated with the firmware will help to record this data with a remote management server for further processing. The messages are defined in JavaScript Object Notation (JSON), which helps to overcome the interoperability issue. The device is smart because it can gather energy usage, detect device faults, and be intimate with the controller for a better operational environment. The associated management servers and mobile applications help to operate the smart device remotely and keep track of the usage statics. The developed low-cost, interoperable smart model is most suitable for two and three-wheeler vehicles.